Свадьба по всем правилам - Шиндина Наталия Геннадиевна (Для дома, для семьи, 2005)
Экземпляры: ф.10 (2005) / Инвентарный номер: 48822 / Цена: / Сис.шифр: 77.056 / Авт.знак: С 24 / ГРНТИ: 13.21 / ББК: 77.056